Una aproximación general sobre el papel del turismo en la sierra de Huelva - Fernández Tabales, Alfonso; Hernández Martínez, Enrique; Marchena Gómez, Manuel; Velasco Martín, Ángel (Huelva en su Historia)
Sin resumen